Rabbit & Robot - Smith, Andrew (Andrew Anselmo), 1959- (New York Simon & Schuster BFYR, 2018)
Stranded aboard the lunar cruise ship Tennessee, Cager Messer and his best friend, Billy, both sixteen, are surrounded by insane robots while watching thirty simultaneous wars turn Earth into a toxic wasteland.
Keywords: Space ships -- Juvenile fiction; Best friends -- Juvenile fiction; Friendship -- Juvenile fiction; Robots -- Juvenile fiction; War -- Juvenile fiction; Space ships -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Robots -- Fiction; Science fiction; Humorous fiction